2022
DOI: 10.1007/s00429-022-02593-9
|View full text |Cite
|
Sign up to set email alerts
|

Proper and common names in the semantic system

Abstract: Proper names are an important part of language and communication. They are thought to have a special status due to their neuropsychological and psycholinguistic pro le. To what extent proper names rely on the same semantic system as common names is not clear. In an fMRI study, we presented the same group of participants with both proper and common names in order to compare associated activations.Both person and place names, as well as personally familiar and famous names were used, and compared with words repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 77 publications
3
5
0
Order By: Relevance
“…Another possible explanation could be the peculiar relevance of conspecifics in human brain processing, be it because of evolutionary (Mahon & Caramazza, 2011) or social (Olson et al, 2013) factors. Both our results and this theoretical view seem to be consistent with the analysis of BOLD activation in (Desai et al, 2022), where it is shown that, when comparing areas selectively activated by either people or place names, the former involve a substantially larger amount of brain voxels (23768mm 3 vs 7035mm 3 ), whereas the latter mostly seem to involve a subset of areas associated with processing of people names.…”
Section: People > Placessupporting
confidence: 91%
See 4 more Smart Citations
“…Another possible explanation could be the peculiar relevance of conspecifics in human brain processing, be it because of evolutionary (Mahon & Caramazza, 2011) or social (Olson et al, 2013) factors. Both our results and this theoretical view seem to be consistent with the analysis of BOLD activation in (Desai et al, 2022), where it is shown that, when comparing areas selectively activated by either people or place names, the former involve a substantially larger amount of brain voxels (23768mm 3 vs 7035mm 3 ), whereas the latter mostly seem to involve a subset of areas associated with processing of people names.…”
Section: People > Placessupporting
confidence: 91%
“…Temporo-parietal clusters are compatible with traditional accounts of proper name processing which have implicated both anterior and posterior temporal areas (Semenza, 2011;O'Rourke & de Diego Balaguer, 2020;Desai et al, 2022). Frontal and posterior midline clusters, where decoding provided higher scores especially when looking for familiarity (Figure 3), may reflect the activity of the Default Mode Network, which is involved in social cognition and episodic (self-related) memory retrieval (Raichle, 2015;Campbell, Louw, Michniak, & Tanaka, 2020;Smallwood et al, 2021;Kaefer, Stella, McNaughton, & Battaglia, 2022).…”
Section: The Timing Of Individual Entities Processingsupporting
confidence: 78%
See 3 more Smart Citations